2013
DOI: 10.1021/jz401958u
|View full text |Cite
|
Sign up to set email alerts
|

Near-Unity Quantum Yield in Semiconducting Nanostructures: Structural Understanding Leading to Energy Efficient Applications

Abstract: Core/shell nanocrystal quantum dots (NQDs) have shown great potential as efficient electroluminescent materials in devices like down-conversion phosphors and light-emitting diodes (LEDs). The efficiency of these devices is nonlinearly enhanced by the use of high quantum yield (QY) materials. Though relatively high QY materials with inherent advantages for use in device applications are achieved by thick-shell CdSe/CdS NQDs, their QY is not anywhere near unity due to lack of correlation of the microstructure wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
66
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 33 publications
3
66
2
Order By: Relevance
“…5,23 Charge carrier delocalization beyond the traditional boundaries of the core and/or shell is well known in literature due to change in material composition as well as energetics. In the current case, this red shift was observed in many literature reports 21,22 which predict a quasi type II nature of CdSe/CdS QDs wherein the electron is delocalized into CdS shell as a result of small CB offset. However, this quasi type II character does not completely explain the observed optical behavior.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…5,23 Charge carrier delocalization beyond the traditional boundaries of the core and/or shell is well known in literature due to change in material composition as well as energetics. In the current case, this red shift was observed in many literature reports 21,22 which predict a quasi type II nature of CdSe/CdS QDs wherein the electron is delocalized into CdS shell as a result of small CB offset. However, this quasi type II character does not completely explain the observed optical behavior.…”
supporting
confidence: 74%
“…This could be due to the need to maintain lower temperatures to retain Cu within the QD 20 while high temperature annealing for extended period of time is necessary for the formation of high quality heterostructures. 21 In this manuscript, we have synthesized Cu doped heterostructures by the appropriate use of ligands as well as suitable variation of temperatures. We have then shown that these Cu doped heterostructures can be used to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 understand the charge localization in a range of heterostructure QDs including type I, type II, inverse type I, quasi type II QDs along with alloys and alloy shell heterostructures using Cu emission and absorption spectra.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Compared with these materials, fl uorescent colloidal semiconductor quantum dots (QDs) are attractive optical probes due to the high photoluminescence (PL) quantum yield (QY), narrow emission, and multiparameter detectable signals. [10][11][12][13] Temperature-dependent studies of the optical properties of QDs have therefore become an emerging area of scientifi c research. Many of these studies are commonly performed at low temperatures to elucidate electronic and excitonic structure in the absence of thermal broadening, and to provide insights into the exciton relaxation processes and excitonphonon interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to high absorption coefficient, conversion efficiency, stability, and significantly low cost synthesis, CdS has continued to be the focus of research. Thin films of CdS have potential applications as solar cell material 2 , lasers 3 , photocatalyist 4 , gas-sensors 5 and light emitting diodes 6 . The extensively used approach to tune the emission range and improve the efficiency of optoelectronic devices is incorporation of impurity atoms in host materials.…”
Section: Introductionmentioning
confidence: 99%